KEUNIKAN TRADISI PERTUNANGAN MASYARAKAT PADANG PARIAMAN - Taufik Hidayat; Yusri Amir (Universitas Islam Negeri Imam Bonjol Padang, 2022)
One of the unique traditions in the casting process in the Padang Pariaman community is